2020
DOI: 10.3390/cancers12071745
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Stem Cell-Inducing Media Activates Senescence Reprogramming in Fibroblasts

Abstract: Cellular senescence is a tumor-suppressive mechanism blocking cell proliferation in response to stress. However, recent evidence suggests that senescent tumor cells can re-enter the cell cycle to become cancer stem cells, leading to relapse after cancer chemotherapy treatment. Understanding how the senescence reprogramming process is a precursor to cancer stem cell formation is of great medical importance. To study the interplay between senescence, stemness, and cancer, we applied a stem cell medium (SCM) to h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…A549 and 293T cells cultured in stem cell medium (SCM) could be converted to cancer stem cells that displayed the phenotype of senescence. Meanwhile, the expression of DNA methyltransferases Dnmt1 and Dnmt3a, histone demethylases Jmjd3 was increased in these cells, which suggested that epigenetic alteration and chromatin remodeling may play a role in cancer stem cell formation and senescence 207 …”
Section: Molecular Mechanisms Of Cancer Stem Cell Senescencementioning
confidence: 95%
“…A549 and 293T cells cultured in stem cell medium (SCM) could be converted to cancer stem cells that displayed the phenotype of senescence. Meanwhile, the expression of DNA methyltransferases Dnmt1 and Dnmt3a, histone demethylases Jmjd3 was increased in these cells, which suggested that epigenetic alteration and chromatin remodeling may play a role in cancer stem cell formation and senescence 207 …”
Section: Molecular Mechanisms Of Cancer Stem Cell Senescencementioning
confidence: 95%
“…Inhibition of EZH2 also leads to SASP production via enrichment of H3K27ac, and loss of H3K27me3, at SASP-related loci (Ito et al, 2018). Overexpression of another histone demethylase, UTX, can also silence H3K27me3 to promote cellular senescence (Perrigue et al, 2020).…”
Section: Senescent Cell Characteristicsmentioning
confidence: 99%
“…Treatment of GC with chrysin, a natural compound frequently present in honey, could significantly upregulate the expression of TET1 and the subsequent elevation of 5-hmC in GC MKN45 cells, thereby inducing cell apoptosis and blocking cell migration/invasion. Thus, the anti-tumor effects of chrysin was mediated through upregulation of TET1 expression in GC, suggesting TET1 as a potentially novel target for GC therapy [119].…”
Section: Natural or Synthetic Small Molecule Compounds Function As Anti-tumor Agents By Upregulation Of Tet1 Expressionmentioning
confidence: 99%